Extended warm temperate zone and opportunities for cropping system change in the Loess Plateau of China. (5th September 2018) - Liu, Zhengjia; Liu, Yansui; Li, Yurui
Abstract : Thermal condition changes largely affect crop phenology, cropping systems and crop field. In this study, we used long‐term (1961–2015) annual accumulated temperature ≥10 °C (AAT10) derived from daily gridded air temperature to investigate the potential implication of AAT10 changes for regional agriculture development in the Loess Plateau (LP). Results showed that an elevation‐dependent spatial pattern of AAT10 was observed. Southeastern LP with low elevation had higher AAT10 and western LP with high elevation had lower AAT10. Across the LP, the start date of 5‐day moving average temperature ( T ¯ ) ≥10 °C (SDT10) showed significantly advanced trends ( p < 0.05), and length of durations of T ¯  ≥ 10 °C (LDT10) and AAT10 both showed significantly increased trends ( p  < 0.05) in the past 55 years. Yet significantly delayed end date of T ¯  ≥ 10 °C (EDT10) was not observed. Compared with EDT10, STD10 contributed more to variations of LDT10 ( R 2  = 0.76, p  < 0.01) and AAT10 ( R 2  = 0.64, p  < 0.01). Besides, this study found that increased temperature in corresponding LDT10 was also responsible for AAT10 increase. Spring temperature contributed more to AAT10 increase relative to autumn and summer temperature. Importantly, area of warm temperate zone (AAT10 ranging 3, 400–4, 500 °C·day) across LP increased from 21.0% in 1960s to 50.3% in 2000–2015 due to climate change. These findings suggest that most LP, especially in regions with good soil conditions and sufficient water resources, had a large potential to develop new cropping systems with two crops per year, which will be helpful for optimizing regional land use and providing decisions on agricultural management. Abstract : Location of the LP, as well as its DEM and distribution of cropland in 2010.